Suicidal Behaviors Among Emerging Adults in Kenyan Universities - Mutwiri, Marion K.; Wambugu, Anne G.; Kinuthia, Jane W.; Gachenia, Lucy (European Scientific Journal, ESJ, 2023)
This study examined the prevalence of suicidal thinking, planning, attempts, and self-harm and the associated psychological stressors in two Kenyan universities. The participants were undergraduate university students aged (18 -29) years. A convergent mixed-method study design was adopted to collect data. Self-administered questionnaires and focus group discussions were carried out among 431 students and six university counselors participated in a three-round Delphi survey. The study instruments were adopted from the Suicide Assessment Five-Step Evaluation & Triage (SAFE-T), Columbia Suicide Severity Rating Scale (C-SSRS), Non-Suicidal Self-Injury Assessment Tool (NSSI-AT), and Emerging Adult Stress Inventory (EASI). A multivariate analysis (MANOVA) was performed. The prevalence rate of suicidal thinking was 17.1%, suicidal planning 5.9%, suicidal attempts 7.8%, and self-harm 5.5%. Female students and private university students have a high prevalence of all suicidal behaviors. Feeling hopeless and depressed, financial difficulty, feeling anxious, family conflicts, and academic challenges were psychological stressors compelling emerging adults to suicidal behaviors. The prevalence of suicidal behaviors was like that found in other studies carried out in other countries. Suicidal behaviors are associated with mental illness symptoms. This should be considered by peers, parents, and university counselors to prevent and intervene in suicidal behaviors.